Allostratigraphy and paleontology of the lower Miocene Chilcatay Formation in the Zamaca area, East Pisco basin, southern Peru. Issue 2 (3rd July 2019) - Di Celma, C.; Pierantoni, P. P.; Malinverno, E.; Collareta, A.; Lambert, O.; Landini, W.; Bosio, G.; Gariboldi, K.; Gioncada, A.; de Muizon, C.; Molli, G.; Marx, F. G.; et al.
ABSTRACT: Based on mapping of laterally traceable stratigraphic discontinuities, we propose a high-resolution allostratigraphic scheme for one of the world's foremost fossil marine vertebrate Lagerstätten: the lower Miocene strata of the Chilcatay Formation exposed along the Ica River near Zamaca, southern Peru. Measured sections combined with 1:10, 000 scale mapping of a 24 km 2 area provide an overview of the stratal architecture, as well as a general facies framework and interpretation of the various depositional settings. As a whole, the Chilcatay alloformation is bounded by the CE0.1 unconformity at the base and the PE0.0 unconformity at the top. An internal Chilcatay surface, termed CE0.2, splits the alloformation into two distinct allomembers (Ct1 and Ct2). The Ct1 allomember comprises three facies associations recording deposition in shoreface, offshore, and subaqueous delta settings. The Ct2 allomember comprises two facies associations, recording deposition in shoreface and offshore settings. Using these data, we place the rich marine vertebrate assemblage in a precise spatial and stratigraphic framework. The well-diversified vertebrate assemblage is dominated by cetaceans (mostly odontocetes) and sharks (mostly lamniforms and carcharhiniforms); rays, bony fish, and turtles are also present. Taxonomic novelties include the first records of baleen whales, platanistids, and eurhinodelphinids from the Chilcatay Formation.